East Germany: Rising incomes, unchanged inequality and the impact of redistributive government 1990 - 92 - Bruce Headey; Peter Krause; Roland Habich (Deutsches Institut für Wirtschaftsforschung (DIW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1993)
What has happened to incomes, inequality and satisfaction with living standards in the first stage of transition from a communist command economy to a market economy in East Germany? This paper tests six hypotheses about the transition to capitalism. Contrary to expectations, real incomes went up not down, net income inequality scarcely increased, and those who were previously advantaged did not become better off aí the expense of the previously disadvantaged. A major reason for the last two results was that the Federal Republic's taxes and benefits, which were much more progressive than the Communist regime's, had the effect of counteracting the increasing inequality of household gross incomes. It is also reported that, although real net incomes increased, satisfaction with living standards declined, probably because East Germans increasingly compared themselves with Western counterparts. Optimism about the future declined in 1991-2 after reaching very high levels in 1990 immediately after the revolution. This paper is based on the first three waves of the East German Socio-Economic Panel Study (SOEP) conducted in June 1990 (N= 4453 respondents in 2179 households), March-April 1991 and March-April 1992.
Keywords: 330; Lebensstandard; Einkommensverteilung; Einkommensumverteilung; Neue Bundesländer